2020
DOI: 10.3390/ani10010082
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Flammulina velutipes Stem Waste on Growth Performance, Fecal Short Chain Fatty Acids and Serum Profile in Weaned Piglets

Abstract: This study was conducted to evaluate the effects of dietary FVS supplementation on growth performance, nutrient digestibility, biochemical profile of serum and fecal short chain fatty acids (SCFAs) production in weaned piglets. In Exp.1, 150 weaned pigs (initial body weight: 6.89 ± 1.17 kg) were allotted to five dietary treatments. The treatment diets included a basal diet and four experimental diets supplemented with 2.5%, 5.0%, 7.5% and 10.0% FVS respectively. The animal trial lasted for 28 days. In Exp.2, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Liu et al [2] demonstrated that 2.5% FVS inclusion in diets had no negative effects on growth performance but impared ATTD of nutrients in piglets, which were similar to the reults in growing-finishing pigs in the current study except for the ADFI results. Song et al [34] reported that dietary inclusion with fermented oyster mushroom byproducts decreased ADG in finishing pigs.…”
Section: Effects Of Dietary Fvs Inclusion On Growth Performance and Nsupporting
confidence: 83%
See 1 more Smart Citation
“…Liu et al [2] demonstrated that 2.5% FVS inclusion in diets had no negative effects on growth performance but impared ATTD of nutrients in piglets, which were similar to the reults in growing-finishing pigs in the current study except for the ADFI results. Song et al [34] reported that dietary inclusion with fermented oyster mushroom byproducts decreased ADG in finishing pigs.…”
Section: Effects Of Dietary Fvs Inclusion On Growth Performance and Nsupporting
confidence: 83%
“…The by-product of FV -Flammulina velutipes stem waste (FVS), has also been produced in large amounts, and the common direct disposal of FVS turned out to be a great threat to our environment and also a huge waste of resources. According to the previous investagation, the average processing cost (mainly due to the electricity consumption) of the FVS powder in China was 43 dollars per ton, while the cost of the raw materials (crude FVS) is almost negligible at present [2]. Thus, the moderate inclusion of FVS in animal diets could greatly reduce the feed cost.…”
Section: Introductionmentioning
confidence: 99%
“…The F. velutipes stem ( FVS ), which is the base of the stalk, is often a waste product in production of the mushroom. Using it as a feed additive not only regulates the immune function, intestinal flora, and lipid metabolism of laying hens and broilers but also avoids environmental pollution due to its incineration or use in landfills ( Mahfuz et al, 2019a ; Liu et al., 2020b ). A study by Nguepi Tsopmejio et al (2021) in our laboratory found that golden needle mushroom improved intestinal inflammation and antioxidant factors in mice through the NF-κB and Nrf2/Keap1 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Piglets and feed were weighed at the beginning, mid‐stage, and the end of the feeding trial to determine the average daily feed intake (ADFI), the ADG, and gain to feed ratio (G/F). The diarrhoea rate was calculated following the formula: Diarrhoea rates (%) =100 × [(Number of pigs showed clinical signs of diarrhoea/Total number of piglets in each pen)/Total trial days] (Liu et al, 2020a).…”
Section: Methodsmentioning
confidence: 99%